Application of the PBL (Problem-Based Learning) Method with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) Approach to Improve Students' Creative Ability in Indonesia - Sumarno Sumarno (PINISI Discretion Review, 2023)
The Indonesian education system has been criticized for its rote learning approach, which emphasizes memorization rather than the application of knowledge. This study aims to explore the application of the Problem-Based Learning (PBL) method with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach to increase students' creativity abilities in Indonesia. PBL emphasizes active learning and application of knowledge in practical scenarios, while STEAM integrates multiple fields to develop a holistic approach to problem-solving. The study was conducted in a classroom setting, and the results showed a significant increase in students' creativity abilities. Students were able to apply their knowledge from different fields to solve problems in a practical and innovative way. The STEAM approach provided a platform for students to collaborate with their peers from diverse fields, which enhanced their problem-solving abilities. Furthermore, the PBL approach helped students to think critically and evaluate multiple solutions to a problem. The findings suggest that the PBL method with the STEAM approach can be an effective approach to enhance students' creativity abilities in Indonesia. The results are particularly relevant to the Indonesian education system, which is working towards enhancing students' creativity and critical thinking abilities. The PBL method with the STEAM approach provides an alternative approach to traditional teaching methods and emphasizes the application of knowledge in practical scenarios.